Etnografando a construção do direito ao acesso à maconha medicinal em um contexto proibicionista: desafios e possibilidades frente aos direitos humanos - Oliveira, Lucas Lopes (2020)
This doctoral research studies the building process of one’s right to use cannabis for therapeutic purposes in Brazil, in which we explore its limits, potentialities and the discursive formations that permeate this subject. We study the discursive constructions on marijuana within the contemporary scientific discourse, as well as the struggle of social movements and their impacts on the legal status of this medicinal plant. We work based on the hypothesis of the existence of a shift in the truth regime that influences the legal definition of the cannabis plant, which allows potential debate for the construction of the right to use medicinal marijuana. The general objective is to explore the construction of the right to obtain therapeutic cannabis through judicial action, social movements and other social agents. Our study will be divided into three parts. Firstly, based on contemporary biopolitics theoretical frameworks, we studied how there was a violation of the healing practices related to popular therapeutic uses of marijuana, by using Criminal Law and the ascending medicine discourse as tools. Secondly, we report the tension involving the prohibiting discourse of marijuana and the recent epistemological changes within the medical discourse, the emergence of the Human Rights discourse, the criminological and dogmatic criticisms of the criminalization of marijuana and the understanding of the right to health as a human right. Finally, we study the emergence of the social movement in defense of medicinal marijuana and the legal and political strategies in the struggle to use this substance in Brazil and Paraíba. This is a qualitative study from an ethnographic perspective and has the genealogical thought of Michel Foucault and the theoretical frameworks of legal sociology as theoretical and methodological guidance. As field research tools, we use documentary research, participant observation and open interview